Research Credibility Analysis And Quality Test Of Supervisors At The Ministry Of Religion, Pangkalpinang City - Kartika Sari; Siti Patimah; Agus Pahrudin; Agus Jatmiko; Koderi (CV. Inara, 2021)
Professional supervisors are supervisors who have competencies including research and development competencies. Research and development competence has eight competency indicators. The challenge in the world of education is the quality and equity of education. One of the components that determine quality is a supervisor who has high professionalism. Two of them relate to the supervisor's ability to master educational research and development concepts and the other six relate to the supervisor's ability to conduct research and educational guidance to teachers. The focus and purpose of this study is to describe and analyze the Competence of Supervisors at the Ministry of Religion of Pangkalpinang City. This research is a qualitative descriptive study. Data collection is done by observation, questionnaires (questionnaires), interviews, and documentation. The results of this study indicate that: (1) The ability of supervisors in the field of research and development aspects of mastery of the concept of approaches, types and research methods is